2021
DOI: 10.1111/ijcp.14502
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological evaluation and an intervention study on timing of food intake in the treatment of obesity

Abstract: Obesity is a disease that causes social, psychological and physical discomfort to the patient. Although there are diet, medication, behavioural and surgical options in its treatment, it progresses with relapse in most cases. Since the underlying cause is not fully understood and causes problems in many organ systems, obesity is still being investigated in all aspects. 1,2 The problem of "why obesity occurs only in some people despite the same calorie intake?", has led studies to focus on feeding time and eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to Beauchamp [ 4 ], depressive symptoms, suboptimal sleep quality and a strong urge to consume food upon night awakenings consist of key elements of the NES psychopathology network and must be set as primary targets for implementing interventions. As a result, research has shown that personalized weight loss programs designed according to the patient’s chronotype can increase the success rate of obesity management [ 102 ]. In parallel, treating chronodisruption may unfold an additional pathway to achieving metabolic health, with a variety of interventions being tested at the moment, including bright light therapy, selective serotonin reuptake inhibitors (SSRIs), psychological counseling (cognitive behavioral therapy) and exogenous melatonin intake [ 16 , 61 , 99 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Beauchamp [ 4 ], depressive symptoms, suboptimal sleep quality and a strong urge to consume food upon night awakenings consist of key elements of the NES psychopathology network and must be set as primary targets for implementing interventions. As a result, research has shown that personalized weight loss programs designed according to the patient’s chronotype can increase the success rate of obesity management [ 102 ]. In parallel, treating chronodisruption may unfold an additional pathway to achieving metabolic health, with a variety of interventions being tested at the moment, including bright light therapy, selective serotonin reuptake inhibitors (SSRIs), psychological counseling (cognitive behavioral therapy) and exogenous melatonin intake [ 16 , 61 , 99 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…By targeting undesirable eating habits like breakfast skipping and late night eating, these lifestyle changes have been shown to effectively support weight loss in obese individuals. [37] A randomized parallel design trial conducted by Jakubowicz et al [38] in overweight/obese women, elucidated that skewing higher daily calories towards breakfast produced significantly greater weight loss and improved insulin sensitivity after 12 weeks, as compared with the same calories exchanged at dinner. A similar caloric distribution was also recommended for people with type 2 diabetes in the management of hyperglycemia, as confirmed in a later randomized controlled trial.…”
Section: Energy Intake Distribution Throughout the Daymentioning
confidence: 99%
“…The circadian system consists of the suprachiasmatic nucleus (also called the master pacemaker) located in the hypothalamus and of peripheral oscillators or “clocks” located in other regions of the brain and most tissues of the body ( 8 , 9 ). Inadequate or mistimed interactions among components of the circadian system with the environmental and/or behavioral cycle can have profound physiological consequences and are associated with multiple adverse health outcomes, which may include disordered eating ( 9 14 ). Early studies suggest that time-of-day clinical features are associated with BE behavior ( 15 , 16 ) and that targeted chronobiological interventions may have therapeutic potential in EDs ( 17 ), suggesting a possible circadian system involvement in BE behavior not yet thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging research supports that food intake timing ( 10 , 19 ), eating behavior and food preference ( 12 , 14 , 20 ) are associated with aspects of the circadian system function in humans but the role that the circadian system may play in BE behavior remains unclear. Given the absence of published studies using best-established methods to study the circadian system in BE behavior, we aimed to systematically review current evidence on circadian-related or proxy measures that can inform the potential role of the circadian system in the etiology, phenomenology, and treatment of BE behavior.…”
Section: Introductionmentioning
confidence: 99%